Development Of Practicum Learning Models Assisted with Practice Guide Videos - Annis Kandriasari; Yeni Yulianti; Rina Febriana; Mohd Nordin, Rumaizah (JTP - Jurnal Teknologi Pendidikan, 2023)
This study aims to develop a practicum learning model assisted by a practicum guide video. The research method used is research and development using the Dick and Carey Educational Research and Development Step System Approach Model and the Bergman and Moore model. The results of the expert one-to-one evaluation, namely material experts, learning design, instructional media and language stated that the practicum model of learning assisted by the practicum guide video was feasible to use. One-to-one student is done by selecting three students whose results are feasible to use. The results of the small group evaluation with an average score of 4.58 for nine students are in the very good category, which can be interpreted as feasible to use; the results of field trials conducted on 30 students obtained 4.57 which can be interpreted as very good. Based on the findings, it can be stated that developing practicum learning model with the use of a practical guide video is feasible and may successfully improve students' knowledge and practice results while meeting the KKNI level 9 requirements.